Large-tow polyacrylonitrile fiber thermal oxidation stabilization reaction control method

The thermal enthalpy value of large tow PAN fibers was measured and controlled by the DSC method, and the thermal oxygen stabilization reaction was accurately regulated, which solved the problem of thermal reaction control in the preparation of large tow carbon fibers, and achieved the preparation of large tow carbon fibers with high performance and low coefficient of variation.

CN119571488AActive Publication Date: 2025-03-07HANGZHOU INST OF ADVANCED MATERIAL BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411633206.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The prior art is difficult to accurately control the thermal oxygen stabilization reaction in the preparation of large tow carbon fibers, resulting in uneven fiber structure, poor mechanical properties, and excessive thermal reaction process, and even a fire risk.

Method used

The thermal enthalpy of the starting and ending states of the large tow PAN fiber was measured by the DSC method, and the thermal enthalpy of the fiber after the end of each temperature zone was controlled, so that the thermal enthalpy difference between the thermal enthalpy and the fiber in the previous state was equal to one N part of the thermal enthalpy difference between the starting and ending state fibers. The deviation was controlled within ±10%, and the thermal oxygen stabilization reaction was accurately regulated.

Benefits of technology

The high-performance and low coefficient of variation of large tow carbon fibers are achieved, with tensile strength ≥4.2GPa, tensile strength coefficient of variation of tensile strength ≤5%, and control operations are simplified, which is suitable for the preparation of large tow and giant tow carbon fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a large-tow polyacrylonitrile (PAN) fiber thermal oxidation stabilization reaction regulation and control method, which comprises the following steps of: in a thermal oxidation stabilization (thermal reaction) process of an N (N is 3, 4, 5 or 6) temperature zone, performing thermal oxidation reaction on the large-tow polyacrylonitrile (PAN) fiber; the method comprises the following steps: respectively measuring enthalpy values in an initial state and a termination state of a thermal oxidation stabilization reaction of the large tow PAN fibers and enthalpy values of the fibers after thermal oxidation stabilization temperature zones are ended through a differential scanning calorimeter (DSC); the difference value between the enthalpy of the sample and the enthalpy of the sample in the previous state is equal to one Nth of the difference value between the enthalpy of the initial state and the enthalpy of the final state, the deviation of the enthalpy difference value is controlled within + / -10%, and the thermal oxidation stabilization reaction degree of each temperature zone is regulated and controlled by using an equal difference enthalpy value method. The large-tow PAN fiber controlled by the method is uniform in thermal reaction heat release and less in redundant reaction, the thermal reaction time is less than or equal to 60 minutes, the tensile strength of the finally prepared large-tow carbon fiber is greater than or equal to 4.2 GPa, and the tensile strength variation coefficient is less than or equal to 5 percent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention belongs to the technical field of carbon fiber preparation, and relates to a method for controlling a thermal oxidation stabilization reaction of large-tow polyacrylonitrile (PAN) fibers. Background Art In recent years, carbon fiber varieties represented by large-tow carbon fiber have achieved significant improvements in both quality and output, and product performance is gradually approaching the level of small-tow carbon fiber T700 and T800. Under the background that large tow and large carbon fiber are becoming the mainstream of carbon fiber development, domestic large tow carbon fiber has developed rapidly. However, the control of the thermal oxidation stabilization reaction of large tow carbon fiber preparation is usually based on the production experience of small tow carbon fiber. For example, large tow fiber is prepared by the control methods such as temperature gradient, residence time, oxidation density (CN201610517888.5) commonly used in small tow fiber. However, the above method cannot accurately reflect the thermal reaction amount of large tow PAN fiber, and cannot make a comprehensive consideration of the whole process of thermal oxidation stabilization, multi-type reactions and other effects. It is highly empirical, resulting in uneven thermal reaction, aggravated fiber structure inhomogeneity, poor mechanical properties, and improper control often leads to redundant reactions in the thermal oxidation stabilization process, which takes too long (≥60min), and even leads to concentrated heat release, hardening of the tow and even fire. The prepared large tow carbon fiber has a large coefficient of variation in performance, and its performance stability is far inferior to that of small tow carbon fiber, so its applicability is limited. In response to the above problems, some researchers have adopted external factors such as atmosphere adjustment (CN201911015644.7) and high-energy irradiation (CN201811235252.7) to release part of the reaction heat in advance and reduce the heat concentration of large-tow fibers in the pre-oxidation process. However, due to the heat resistance of PAN precursor fibers, the reaction heat released in advance is small, or there is a risk of breaking the PAN macromolecules. In addition, there are major changes to the production equipment, and precise control and high preparation costs are still a problem. Summary of the invention In order to efficiently and accurately regulate the thermal reaction during the thermal oxidation stabilization process of large-tow PAN fibers, and then homogenize and regulate the internal structure of the fibers, and prepare high-performance, low-coefficient-of-variation large-tow carbon fibers, the present invention provides a control method for the thermal oxidation stabilization reaction of large-tow PAN fibers.

[0004] To realize the present invention, the technical solution is as follows:

[0005] First, in the thermal oxidation stabilization of 3 to 6 temperature zones (the number of temperature zones is set to N), the enthalpy values ​​H1 and H2 of the initial and final states of the large-tow PAN fiber are respectively measured by the DSC method to obtain the reaction heat △H=H1-H2. The test conditions of DSC are heating rate: 0.5-20℃ / min, test mass: 0.5-20mg, heating range: room temperature to 500℃, test atmosphere: air. Then the fiber enthalpy value after each temperature zone is controlled so that the difference between its enthalpy and the enthalpy of the fiber in the previous state is equal to one Nth of the difference between the fiber enthalpy in the initial state and the final state, and the deviation is controlled within ±10%. The obtained large-tow pre-oxidized fiber is then subjected to low-temperature carbonization, high-temperature carbonization and other processes to finally obtain large-tow carbon fiber.

[0006] The unit of thermal enthalpy is J / g.

[0007] The initial state fiber is PAN raw fiber with a density of 1.180-1.205 g / cm 3 , diameter 9~15um.

[0008] The final state is the fiber after the thermal oxidation stabilization is completed, and the density is 1.335-1.375 g / cm 3 According to the standard GB / T30019-2013, the cyclization degree is ≥80%, according to the infrared spectrum 1580cm -1 and 2240cm -1 The absorption peak intensity near 1580cm -1 ) / [I(2240cm -1 )+I(1580cm -1 )] calculated, the orientation degree is ≥70%, determined by the sonic velocity method.

[0009] The tensile strength of the large-tow PAN fiber is ≥5.0 cN / dtex.

[0010] The polymerization solvent route of the large-tow PAN fiber is one of the organic solvent routes such as DMSO, DMAc, DMF, etc.

[0011] The K number specification of the large-tow PAN fiber is 48K-200K.

[0012] By this method, the thermal oxidation stabilization reaction time of PAN fiber is ≤60min, and the tensile strength of the obtained large-tow carbon fiber is

[0013] ≥4.2GPa, tensile strength variation coefficient ≤5%. It also has the following advantages:

[0014] 1. No need to change equipment, the control operation method is simple and effective.

[0015] 2. Suitable for the preparation of large tow or even giant tow carbon fiber (≥60K). DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0017] Comparative Example 1: 48K polyacrylonitrile fiber-NO1 is used, and the degree of reaction is controlled by the temperature gradient principle. The first temperature zone is set to 220°C, with a total of 4 temperature zones, and the residence time of each temperature zone is 15min. The total pre-oxidation time is 60min. The temperature of each temperature zone is controlled to change in an arithmetic step, and the temperature gradient is 15±1.5°C, that is, 235°C in the second temperature zone, 250°C in the third temperature zone, and 265°C in the fourth temperature zone. The obtained pre-oxidized fiber continues to undergo low-temperature carbonization (350-1000°C, 4-8 temperature zones, residence time 0.5-5min, N2 atmosphere, draft ratio 1-1.2,) and high-temperature carbonization (1000-1800°C, 4-8 temperature zones, residence time 0.5-5min, N2 atmosphere, draft ratio 0.94-1), and finally a large tow carbon fiber is obtained. The temperature, thermal enthalpy value, and density of each temperature zone are as shown in the following table.

[0018] parameter 48K-PAN-NO1 The first temperature zone Second temperature zone The third temperature zone The fourth temperature zone Temperature / ℃ Room temperature 220 235 250 265 <![CDATA[Enthalpy / J*g -1 > 2200 2000 1900 1500 900 <![CDATA[Enthalpy difference / J*g -1 > / 200 100 400 600 <![CDATA[Density / g*cm -3 > 1.192 1.233 1.264 1.282 1.361

[0019] The properties of the obtained large-tow carbon fiber are shown in the following table.

[0020]

[0021] Comparative Example 2: Using 48K polyacrylonitrile fiber-NO1, the density gradient principle was used to control the pre-oxidation density in each temperature zone, and the density gradient was 0.04±0.004g / cm 3 There are 4 temperature zones in total, the residence time in each temperature zone is 10 minutes, and the total pre-oxidation time is 40 minutes. The obtained pre-oxidized fiber continues to undergo low-temperature carbonization (350-1000℃, 4-8 temperature zones, residence time 0.5-5 minutes, N2 atmosphere, draft ratio 1-1.2) and high-temperature carbonization (1000-1800℃, 4-8 temperature zones, residence time 0.5-5 minutes, N2 atmosphere, draft ratio 0.94-1), and finally obtains large-tow carbon fiber. The temperature, thermal enthalpy value and density of each temperature zone are shown in the following table.

[0022]

[0023]

[0024] The properties of the obtained large-tow carbon fiber are shown in the following table.

[0025]

[0026] Example 1: Using 48K polyacrylonitrile fiber-NO1, thermal reaction 4 temperature zones, the initial state raw fiber density is 1.192g / cm 3 The final state pre-oxidized fiber density is 1.351g / cm 3 The thermal enthalpy of the fiber in the initial and final states was measured to be 2200 J / g and 1000 J / g respectively. The thermal enthalpy change was controlled to be 300±30 J / g. The residence time in each temperature zone was 10 min and the total time was 40 min. The thermal enthalpy value of each temperature zone and the corresponding thermal reaction temperature are as follows.

[0027] parameter 48K-PAN-NO1 The first temperature zone Second temperature zone The third temperature zone The fourth temperature zone <![CDATA[Enthalpy / J*g -1 > 2200 1920 1610 1300 1000 <![CDATA[Enthalpy difference / J*g -1 > / 280 310 310 300 Temperature / ℃ Room temperature 227 242 253 260 <![CDATA[Density / g*cm -3 > 1.192 1.235 1.282 1.320 1.351

[0028] The large tow pre-oxidized fiber is subjected to the same low-temperature carbonization and high-temperature carbonization as the comparative example to obtain large tow carbon fiber with the following properties:

[0029]

[0030] Example 2: Using 48K polyacrylonitrile fiber-NO1, thermal reaction 6 temperature zones, the initial state raw fiber density is 1.192g / cm 3 The final state pre-oxidized fiber density is 1.375g / cm 3 The thermal enthalpy of the fiber in the initial and final states was measured to be 2200 J / g and 790 J / g respectively. The thermal enthalpy change was controlled to be 235±23.5 J / g. The residence time in each temperature zone was 10 min and the total time was 60 min. The thermal enthalpy value of each temperature zone and the corresponding thermal reaction temperature are as follows.

[0031]

[0032] The properties of the large-tow carbon fibers obtained after low-temperature carbonization and high-temperature carbonization of the large-tow pre-oxidized fibers are as follows.

[0033]

[0034]

[0035] Example 3: Using 48K polyacrylonitrile fiber-NO1, the initial raw fiber density is 1.192g / cm 3 The final pre-oxidized fiber density is 1.345 g / cm 3 The thermal enthalpy of the fiber in the initial and final states was measured to be 2200 J / g and 1120 J / g respectively. There were three temperature zones for thermal reaction, and the thermal enthalpy change was controlled to be 360±36 J / g. The residence time in each temperature zone was 10 min, and the total time was 30 min. The thermal enthalpy value of each temperature zone and the corresponding thermal reaction temperature are as follows.

[0036] parameter 48K-PAN-NO1 The first temperature zone Second temperature zone The third temperature zone <![CDATA[Enthalpy / J*g -1 > 2200 1845 1480 1120 <![CDATA[Enthalpy difference / J*g -1 > / 355 365 360 Temperature / ℃ Room temperature 231 248 258 <![CDATA[Density / g*cm -3 > 1.192 1.235 1.286 1.345

[0037] The properties of the large-tow carbon fibers obtained after low-temperature carbonization and high-temperature carbonization of the large-tow pre-oxidized fibers are as follows.

[0038]

[0039] Example 4: Using 60K polyacrylonitrile fiber-NO2, the initial raw fiber density is 1.199g / cm 3 , with 1.345g / cm 3 The final pre-oxidized fiber density is obtained by measuring the heat enthalpy of the fiber at the initial and final states, which are 2750 J / g and 1125 J / g respectively. The thermal reaction has 4 temperature zones, with a residence time of 10 min in each zone and a total time of 40 min. The heat enthalpy values ​​of each zone and the corresponding thermal reaction temperatures are as follows.

[0040] parameter 60K-PAN-NO2 The first temperature zone Second temperature zone The third temperature zone The fourth temperature zone <![CDATA[Enthalpy / J*g -1 > 2750 2350 1950 1525 1125 <![CDATA[Enthalpy difference / J*g -1 > / 400 400 425 400 Temperature / ℃ Room temperature 230 238 248 257 <![CDATA[Density / g*cm -3 > 1.199 1.205 1.256 1.306 1.345

[0041] The properties of the large-tow carbon fibers obtained after low-temperature carbonization and high-temperature carbonization of the large-tow pre-oxidized fibers are as follows.

[0042]

[0043] Example 5: Using 200K polyacrylonitrile fiber-NO3, the initial raw fiber density is 1.195g / cm 3 , with 1.36g / cm 3 The final pre-oxidized fiber density is obtained by measuring the heat enthalpy of the fiber at the initial and final states, which are 2380 J / g and 1000 J / g respectively. The thermal reaction has 6 temperature zones, with a residence time of 10 min in each zone and a total time of 60 min. The heat enthalpy values ​​of each zone and the corresponding thermal reaction temperatures are as follows.

[0044]

[0045] The properties of the large-tow carbon fibers obtained after low-temperature carbonization and high-temperature carbonization of the large-tow pre-oxidized fibers are as follows.

[0046]

[0047] Note: The heating rate of the thermal enthalpy test in the embodiment is 5°C / min, and the mass is 5 mg.

Claims

1. A method for controlling the thermal oxidation stabilization reaction of large-tow polyacrylonitrile fiber, which is based on the principle of differential thermal enthalpy control. In the thermal oxidation stabilization of N (N is 3 to 6) temperature zones, first, in an air atmosphere, the heating rate and mass are fixed, and the thermal enthalpy values ​​H1 and H2 of the initial and final states of the large-tow PAN fiber are measured by differential scanning calorimetry (DSC) in the range of room temperature to 500°C to obtain the reaction heat △H=H1-H2; then, fiber sampling is performed in the state after each temperature zone ends, and the thermal enthalpy value of the fiber after each temperature zone ends is controlled so that the difference between its thermal enthalpy and the thermal enthalpy of the fiber in the state after the previous temperature zone ends is equal to one N of the difference between the thermal enthalpy of the fiber in the initial state and the final state, that is, △H / N, and the deviation is controlled within ±10%. By this method, the thermal oxidation stabilization reaction time of PAN fiber is ≤60min, and the tensile strength of the obtained large-tow carbon fiber is ≥4.2GPa, and the coefficient of variation of tensile strength is ≤5%.

2. The method according to claim 1, characterized in that The unit of thermal enthalpy is J / g.

3. The method according to claim 1, characterized in that The test heating rate is 0.5-20°C / min, preferably 1-10°C / min.

4. The method according to claim 1, characterized in that The test mass is 0.5 to 20 mg, preferably 1 to 10 mg.

5. The method according to claim 1, characterized in that The initial state fiber is PAN raw fiber, with a density of 1.180-1.205 g / cm3, a diameter of 9-15 um, and a tensile strength of ≥5.0 cN / dtex.

6. The method according to claim 1, characterized in that The final state is the fiber after the thermal oxidation stabilization is completed, with a density of 1.335-1.375 g / cm3, a cyclization degree ≥80%, and an orientation degree ≥70%.

7. The method according to claim 1, characterized in that The polymerization solvent route of the large-tow PAN fiber is one of the organic solvent routes such as DMSO, DMAc, DMF, etc.

8. The method according to claim 1, characterized in that The K number specification of the large-tow PAN fiber is 48-200K.

Citation Information

Patent Citations

  • Pre-oxidation method for preparation of large-tow carbon fiber

    CN106222803A

  • Preparation method of polyacrylonitrile-based large tow carbon fibers

    CN111088560A

  • Pre-oxidation method of polyacrylonitrile-based fibers and preparation method of carbon fibers

    CN112708967A

  • Stabilizing polyacrylonitrile precursor yarns

    CN102612576A

  • Acrylic fibers, preparation method of acrylic fibers, and preparation method of carbon fibers

    CN113862811A

Cited By

  • Method for evaluating uniformity of large-tow PAN pre-oxidized fiber

    CN122409747A